Unveiling Narcissistic Tendencies Through Vulnerability and Vanity in Howl Jenkins in Howl’s Moving Castle by Diana Wynne Jones - Via Agustina; Thohiriyah Thohiriyah (Universitas Muhammadiyah Malang, 2025)
This study begins with the problem of the representation of narcissistic traits in literary works, which are often perceived narrowly only through arrogant and exhibitionist behavior, while the dimension of emotional vulnerability is often overlooked. This study aims to analyze the character of Howl Jenkins in Diana Wynne Jones's novel Howl's Moving Castle by emphasizing two main aspects, namely vulnerability (vulnerability) and arrogance (self-conceit), and connecting them with the theoretical framework of self-psychology. The study uses a qualitative descriptive method with a careful reading technique. Primary data is presented in the form of a novel text, explained through quotations, interactions, and narratives that display Howl's narcissistic traits. In contrast, secondary data is obtained from relevant articles, journals, and books on narcissism and emotional vulnerability. The results show that Howl's narcissism cannot be understood singly, but rather exists as a dialectic between vulnerability and arrogance. His emotional vulnerability is manifested in fear of anxiety, anxiety, and realizing identity. At the same time, arrogance serves as a protective mechanism to cover his fragility, manifesting as flamboyance and an obsession with appearance. These findings demonstrate that literary works can be an effective medium for illustrating multidimensional psychological dynamics and make theoretical contributions to the development of the concept of narcissism in contemporary psychology. This research also makes practical contributions to literature teaching by opening a reflective space for readers to understand the complexity of human emotions through fictional narratives.